Introductory editorial: T.I.: Advances in Environmental Geochemistry - Carol, Eleonora Silvina (2020)
A field as broad as geochemistry has evolved naturally to be subdivided, at various levels, into sub-disciplines. These sub-disciplines are distinguished from each other in several different ways and there is considerable overlap betweenthem in many cases. Geochemistry involves the study of the distribution, proportion, and association of chemical elements of the earth?s crust that are present in different matrices such as water (fresh, saline, residual, rain, superficial and groundwater), soils, minerals, sediments, rocks and air.The Argentine meetings of Geochemistry of the Surface RAGSU) have been held since 2009 with a periodicity of 2 and 3 years. The main research centers of the country participate in the organization and the groups that work specifically in the Geochemistry of the Surface can meet at these events.